Education Supervision in Improving Teacher Professionalism in State Elementary School 103024 - Muhammad Irvan Marsya; Rahmiatul Zuhro; Siddiq Permadi; Supardi Supardi; Zahara Ahmad Fauzi; Rizhani Masrura; Inom Nasution (Universitas Muhammadiyah Enrekang, 2022)
This research was conducted to see how the challenges of teachers in the online learning system carried out by schools or educational institutions are whether there is a very big obstacle or a small obstacle. Therefore we want to interview one or several teachers to get data or results from what they feel during the current online learning system whether online learning is running effectively or is it a very big obstacle. And at this time we will see it in the research that we will do.